2001
DOI: 10.1210/jcem.86.10.7912
|View full text |Cite
|
Sign up to set email alerts
|

Direct Action of Melatonin in Human Granulosa-Luteal Cells

Abstract: The direct involvement of melatonin in modulation of ovarian steroidogenesis, the high levels of melatonin found in human follicular fluid, and the presence of melatonin binding sites in the ovary led us to hypothesize that melatonin acts as a modulator of ovarian function. In contrast to the hypothalamus and pituitary, the mechanism of melatonin action at the level of the ovary is still poorly understood. In the present study, we investigated the gene expression of the two different forms of melatonin recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
104
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(114 citation statements)
references
References 63 publications
4
104
0
6
Order By: Relevance
“…Melatonin is concentrated in human ovarian FF relative to the level in plasma (20)(21)(22), and melatonin alters granulosa cell (GC) steroidogenesis and follicular function in hen (44), hamster (45), and humans (8,(46)(47)(48). Melatonin binding sites are detected in the membrane fraction of human GCs (7) and both MT1 and MT2 melatonin receptors were identified in human GC/luteal cells (8,49) and in rat ovaries (antral follicles and corpus luteum [CL]) (50).…”
Section: Melatonin Receptors In the Ovarymentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin is concentrated in human ovarian FF relative to the level in plasma (20)(21)(22), and melatonin alters granulosa cell (GC) steroidogenesis and follicular function in hen (44), hamster (45), and humans (8,(46)(47)(48). Melatonin binding sites are detected in the membrane fraction of human GCs (7) and both MT1 and MT2 melatonin receptors were identified in human GC/luteal cells (8,49) and in rat ovaries (antral follicles and corpus luteum [CL]) (50).…”
Section: Melatonin Receptors In the Ovarymentioning
confidence: 99%
“…This is supported in part by the demonstration of melatonin receptors in the suprachiasmatic nuclei in the brain and pars tuberalis of the pituitary (5,6). Also, the demonstration of melatonin receptors in the ovary indicates multiple sites at which melatonin may influence the reproductive system (7,8).…”
mentioning
confidence: 91%
“…Extra-hypothalamic pathway of action of melatonin on oocyte maturation Demonstration of melatonin binding sites in mammalian reproductive organs (Yie et al 1995;Woo et al 2001) raised the possibility of direct action of this indole amine on the gonad. However, the results of previous in vitro studies on the oocytes of carp C. carpio (Popek et al 1991(Popek et al , 1996 and killifish F. heteroclitus (Cerda et al 1997) did not show any effect of melatonin on oocyte maturation.…”
Section: Dose-and Duration-dependent Influences Of Exogenous Melatonimentioning
confidence: 99%
“…Some authors (10,11) have shown evidence of melatonin's direct action on the ovaries. In the reproductive system, melatonin may interact with sex steroids and interfere with ovarian function.…”
mentioning
confidence: 99%